The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jcla.22907
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of neutrophil gelatinase‐associated lipocalin in ischemic stroke patients with acute kidney injury

Abstract: BackgroundAcute kidney injury (AKI) has become a common complication of acute ischemic stroke (AIS) and may have a significant impact on the clinical outcomes. Neutrophil gelatinase‐associated lipocalin (NGAL), an acute phase protein, has been identified as a novel biomarker for acute kidney impairment. Here, we studied the early expression of NGAL in AIS patients with AKI and its clinic value in predicting and diagnosis of AKI after stroke.MethodsA total of 205 subjects diagnosed as first‐ever AIS were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A previous study reported that urinary liver-type fatty-acid binding protein (L-FABP) was independently associated with the development of AKI and 90-day mortality in critically ill patients with IS ( 6 ). Xiao et al found that serum neutrophil gelatinase-associated lipocalin (NGAL) could predict AKI in patients with IS ( 7 ). However, the above-mentioned biomarkers are not easy to obtain in the ICU setting, and finding relatively clinically often-used indicators may help ICU clinicians in identifying those at high risk.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that urinary liver-type fatty-acid binding protein (L-FABP) was independently associated with the development of AKI and 90-day mortality in critically ill patients with IS ( 6 ). Xiao et al found that serum neutrophil gelatinase-associated lipocalin (NGAL) could predict AKI in patients with IS ( 7 ). However, the above-mentioned biomarkers are not easy to obtain in the ICU setting, and finding relatively clinically often-used indicators may help ICU clinicians in identifying those at high risk.…”
Section: Introductionmentioning
confidence: 99%
“…NGAL has been accepted by many nephrologists as a biomarker of early acute and chronic kidney injury, and some scholars also regard it as a neuroin ammatory marker [15,16,32]. This study found that the level of NGAL in IS patients was higher than that of HC and DC, while the levels of the other four renal function markers were only higher than HC.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, its serum level gradually increases with the continuous progress of CKD [14]. Many studies have found that NGAL can also be used as a marker of neuroin ammation and related behavioral dysfunction [15,16]. The increase of NGAL in brain tissue can aggravate amyloid-β-induced toxicity, leading to neurodegenerative changes in the brainstem nucleus [17].…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 16 , 17 , 18 , 19 Patients with acute ischemic stroke with AKI were also shown to have high urine and plasma NGAL levels. 20 NGAL appears to be most sensitive and specific in homogeneous patient populations with temporally predictable forms of AKI. Published studies have also identified age as an effective modifier of NGAL’s performance as an AKI biomarker, with better predictive ability in children (overall AUC‐ROC, 0.93) than in adults (AUC‐ROC, 0.78).…”
Section: Discussionmentioning
confidence: 95%